Electromagnetic Interference Shielding and Characterization of Ni2+ Substituted Cobalt Nanoferrites Prepared by Sol-Gel Auto Combustion Method - Rezhna Kuekha; Tahseen H. Mubarak; Bruska Azhdar (Advances in Materials Science and Engineering, 2022)
The structural, magnetic, and dielectric properties of a series of Ni2+ substituted cobalt nanoferrite particle samples with the composition Co1−xNixFe2O4 (where x = 0.0 ≤ x ≤ 1.0) synthesized by using the sol-gel auto combustion route are presented in this report. The electromagnetic interference shielding of Co1−xNixFe2O4/PVA nanocomposite films has been determined in the microwave X-band (8.2–12.4 GHz) frequencies. X-ray analysis revealed the single-phase formation of nickel-substituted cobalt nanoferrite samples. The decreasing trend of lattice parameters with Ni2+ substitution indicates the incorporation of Ni2+ into the crystal structure, obeying Vegard’s law. FTIR showed the absorption bands at 560–590 cm−1 (v1) and 390–400 cm−1 (v2) were attributed to (A-site) tetrahedral and (B-site) octahedral groups complex, respectively which confirm the spinel structure of the samples. Field emission scanning electron microscopy showed agglomerated grains of different sizes and shapes in the morphological observation. EDS reveals the chemical composition of the prepared samples. TEM analysis revealed that the synthesized particles were nearly monodisperse, show to be roughly spherical in shape, and have a polycrystalline nature. The dielectric constant and loss tangent (tanδ) is found to decrease with increasing frequency which shows normal behavior for ferrimagnetic materials. The magnetic properties determined using VSM have substantially changed with the substitution of Ni2+ ions. The saturation magnetization and the experimentally magnetic moment are observed to decrease with an increase in Ni2+ content x. A series of Co1−xNixFe2O4/PVA nanocomposite films are prepared by applying simple, rapid, and inexpensive methods for EMI shielding materials. The vector network analyzer data were used to evaluate the electromagnetic interference (EMI) shielding properties of the Co1−xNixFe2O4/PVA samples. At 9.2 GHz, a study of reflection loss showed a minimum reflection loss (RL) of −32.08 dB. Also, the synthesized Co1−xNixFe2O4/PVA nanocomposite samples show improved performance for EMI efficiency which proves the utility of this doping. With this low RL value, the results and techniques also promise a simple, effective approach to achieve light-weight Co1−xNixFe2O4/PVA nanocomposite films and make it excellent microwave absorbers, capable of working at gigahertz frequencies for application potentials in EMI shielding material, communication, radar stealth technology, and electronic warfare.